2014
DOI: 10.1590/s1516-8913201402262
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Histomorphometric Evaluation of Zebu Bull Breeds

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…In the present study, the values observed for the volumetric proportions of the testicular parenchyma constituents were in line with those observed by Andreussi et al [1], with 80.9% of the testicular parenchyma occupied by seminiferous tubules. However, this result differed from the overall average of all other breeds as, according to Andreussi et al [1], animals of the Nelore breed had a higher volume of seminiferous tubules compared to all other Zebu breeds studied.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the values observed for the volumetric proportions of the testicular parenchyma constituents were in line with those observed by Andreussi et al [1], with 80.9% of the testicular parenchyma occupied by seminiferous tubules. However, this result differed from the overall average of all other breeds as, according to Andreussi et al [1], animals of the Nelore breed had a higher volume of seminiferous tubules compared to all other Zebu breeds studied.…”
Section: Discussionsupporting
confidence: 93%
“…The gonadosomatic index in the Gir breed found in the present study (0.12%) was similar to that observed in other studies performed on zebuine cattle. Andreussi et al [1] also found a gonadosomatic index of 0.12% in Gir animals, with an average of 0.13% in the Nelore, Nelore mocho, Gir, Tabapuã, and Guzerá breeds. In young taurine animals of the Shorthorn breed, Swierstra [27] obtained an GSI of 0.8%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, no significant differences were observed in pixel intensities between the right and left testicles, reinforcing observations by Aravindakshan et al (2000), Cardilli et al (2009), andPinho et al (2013). The observed homogeneity has already been reported in previous studies, in which fragments extracted from different sections of the testicle presented morphometric counts that were not significantly different from each other (Andreussi et al 2014).…”
Section: Resultssupporting
confidence: 86%
“…Significant differences in daily sperm production have been observed in sexually mature Zebu bulls (Andreussi et al 2014), therefore, a new method to track these differences would significantly improve breeding options.…”
Section: Introductionmentioning
confidence: 99%